PENGARUH PELATIHAN, PENGEMBANGAN KARIR DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PDAM KABUPATEN GIANYAR - Ni Komang Dewi Puspa Lala; I Gede Gama; Gede Bayu Surya Parwita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
PDAM Gianyar Regency is a regional company that provides clean water to the community, especially the people of Gianyar Regency. Therefore, as an agency that implements public services, PDAM Gianyar Regency is expected to provide satisfactory performance. But currently PDAM Gianyar Regency is experiencing problems in terms of employee performance. Lack of training for employees, not being able to implement career development and encourage and motivate employees to improve employee performance, and the lack of competency application in doing a job based on their work knowledge experience. This study aims to test and obtain empirical evidence of the effect of training, career development, and competence on employee performance at PDAM Gianyar Regency. The population in this study were all employees of PDAM Gianyar Regency as many as 70 people, the sampling technique used was saturated sampling technique, so that the entire population was sampled. The analytical tool used is multiple linear analysis, classical assumption test, t test, and F test. The results of this study indicate that training has a positive and significant effect on employee performance at PDAM Gianyar Regency. Career development has a positive and significant effect on employee performance at PDAM Gianyar Regency. Competence has a positive and significant effect on employee performance at PDAM Gianyar Regency. It is recommended to PDAM Gianyar Regency to encourage employees to work more carefully, effectively and efficiently in order to improve the quality of their work so that they are in line with the stated agency goals.